Retrospective Analysis in Lower Limb Reconstruction: Propeller Perforator Flaps versus Free Flaps - Cajozzo, Marta; Toia, Francesca; Innocenti, Alessandro; Tripoli, Massimiliano; Zabbia, Giovanni; D'Arpa, Salvatore; Cordova, Adriana (Journal of Reconstructive Microsurgery, 2017)
Background Technical advancements and increasing experience in the management of soft tissue defects in lower extremities have led to the evolution of decisional reconstructive algorithms. Both propeller perforator flaps (PPFs) and free flaps (FFs) proved to be useful methods of reconstruction for lower extremities defects, offering alternative reconstructive tools. We present a case series of PPFs and FFs for reconstruction of lower limbs defects, analyzing and comparing treatment and outcomes.Methods Through a retrospective analysis, we report our experience in performing PPFs or FFs for reconstruction of soft tissue defects of the lower extremities, in patients admitted between 2010 and 2015 at the Department of Plastic and Reconstructive Surgery, University of Palermo. In these patients, we evaluated location and causes of defects, types of flaps used, recipient vessels, complications, time to healing, and aesthetic outcome.Results A primary healing rate was obtained in 13 patients for PPF and 16 cases for FF. Revision surgery for partial skin necrosis was required in eight cases (PPF: four and FF: four). Recovery time and hospitalization period were eventually shorter in patients with FFs, due to lower rate of complications and revision surgery.Conclusion In the past years, our indications for reconstruction with PPFs in the lower limb have become more restricted, while we favor reconstruction with FFs. Recommendations are provided to orient surgical treatment in small, medium, and large lower limb defects.
Keywords: lower limb reconstruction; propeller perforator flap; free flap